KAJIAN IMPLEMENTASI PERATURAN DAERAH KOTA YOGYAKARTA NOMOR 1 TAHUN 2014 TENTANG PEMBERIAN ASI EKSKLUSIF - Dian Anggraini; Mufdillah Mufdillah (Universitas Aisyiyah Yogyakarta, 2015)
The purpose of this study was to investigate the study of Yogyakarta regulation no 1 year 2014 about exclusive breastfeeding. The study employed qualitative study using inductive data analysis. The research subject was breastfeeding mothers and KP-mothers motivator taken through purposive sampling. The data where taken through in depth interview and focus group discussion. The research instrument was an interview guideline. The validity of the data used triangulation data. The on-going implementation are IMD, exclusive breast milk, cooperative care, and administrative sanction. The unaccomplished implementation is reward. The implementation which needs to be improved are monitoring, providing lactation room at offices and public facilities, and utilizing baby formula and other baby's products. The conclution is the implementation of Yogyakarta city regulation has not realized yet because it does not run as the policy in the regulation of this area.Keywords: implementation study, Yogyakarta regulation no 1 year 2014 about breastfeeding